Rama Co-RADS: Cutting-edge tool for improved communication in management and treatment of COVID-19 patients in Thailand - Suwatanapongched, Thitiporn; Nitiwarangkul, Chayanin; Arnuntasupakul, Vanlapa; Kiertiburanakul, Sasisopin (The ASEAN Journal of Radiology, 2021)
In Thailand, the rapid and constant rise in the number of confirmed COVID-19 cases, together with the increasing number of patients requiring respiratory and other medical life support during the third wave of COVID-19, has drastically overwhelmed the existing country’s healthcare facilities, physicians, and other healthcare workers. Hence, early identification of vulnerable patients at risk and early COVID-19 pneumonia is crucial for timely management and treatment by antivirals or corticosteroids to prevent them from developing severe COVID-19 pneumonia. A prompt chest X-ray report with clear and concise information at baseline screening in alternative healthcare facilities, especially in resource-constrained conditions, is essential. The article presents the incorporation of Rama Co-RADS (a categorical assessment scheme for chest X-ray findings for diagnosing pneumonia in patients with confirmed COVID-19). Its use facilitates a rapid, clear, and concise X-ray report despite the various levels of radiologists’ experience. Comprehensibleand consistent chest X-ray information successfully reduces the time lapse and communication gap among medical staff and assists on-duty, frontline physicians to make prompt and more accurate decisions regarding the management and treatment of COVID-19 patients in accordance with the current national guideline.